MODEL KOMUNIKASI KYAI LULUSAN KAIRO MESIR MENGGUNAKAN BAHASA ARAB DI SANTRI DI PONDOK PESANTREN MODERN SYAMSUDIN BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU RIAU - Wahyu Nurhalim (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
The existence of Islamic boarding school (pesantren) can’t be separated from the figure of a clerics (kyai)and the communication between clerics and students (santri). Using qualitative research approach, thisstudy aims to to prepare, understand and analyze communication models between clerics and students inPesantren Modern Syamsuddin B. Communication Model between clerics and students in Islamicboarding school is influenced by the concept of Morals, status and charisma of clerics. Moral education is away to establish communication that facilitates management of transfer of knowledge to students. Status andcharisma of clerics are enhancer factor communicator legitimacy in the context of Islamic boarding school. Theresearch concludes that the construction of communications models of clerics and students was formed by high-intensity interactions between clerics and students.